Efektivitas Metode Pembelajaran Interaktif Dalam Meningkatkan Pemahaman Aqidah Akhlak MTs Mualimin Univa Medan - Siregar, Zainab; Zuliana, Zuliana (EL-EMIR Institute, 2024)
This research aims to examine the effectiveness of interactive learning methods in improving student’s comprehension of Aqidah Akhlak at MTS Mualimin UNIVA Medan. The study arose from the challenge of low student engagement and interest in Aqidah Akhlak when taught through conventional methods, which often results in limited understanding of the subject matter. To address this issue, interactive learning approachess are expected to foster a more engaging and participatory classroom atmosphere. This research adopts a qualitative approach, utilizing observation and interviews with teachers and students for data collection. The research subjects include seventh and eight-grade students who have experienced the interactive method over a learning period. The findings demonstrate that the use of interactive learning methods significantly boosts student participation in the learning process. Moreovor, there is a noticeable positive shift in student attitudes and behaviors, especially in the application of ethical values in their daily lives. The study concludes that interactive learning methods are effective in deepening student’s understanding of Aqidah Akhlak content.